Proceedings of the Thirteenth Conference on Applied Linguistics (CONAPLIN 2020) 2021
DOI: 10.2991/assehr.k.210427.041
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal and Supraliminal Effects of Metaphors on Brain Activity

Abstract: Hypnotherapists commonly use metaphors in their suggestions. In hypnotherapy suggestions, metaphors contain a spoken effect. However, until now, metaphors in hypnotherapy speech on brain activity have not been specifically studied. The purpose of this study was to obtain a description of which brain activity appears influenced by different types of metaphors in hypnotherapy speech. The method used in this research is one shot case study. Data collected from one participants in the form of electroencephalograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Future studies should go beyond this stream of research through the lens of neuroscience. Nurhadi and Saifullah (2021) revealed that both supraliminal and subliminal stimuli can make alpha brainwaves increase and beta brainwaves decrease [ 84 ]. Moreover, everyone’s brains deal with supraliminal and subliminal messages differently [ 84 ].…”
Section: General Discussion Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should go beyond this stream of research through the lens of neuroscience. Nurhadi and Saifullah (2021) revealed that both supraliminal and subliminal stimuli can make alpha brainwaves increase and beta brainwaves decrease [ 84 ]. Moreover, everyone’s brains deal with supraliminal and subliminal messages differently [ 84 ].…”
Section: General Discussion Implications and Conclusionmentioning
confidence: 99%
“…Nurhadi and Saifullah (2021) revealed that both supraliminal and subliminal stimuli can make alpha brainwaves increase and beta brainwaves decrease [ 84 ]. Moreover, everyone’s brains deal with supraliminal and subliminal messages differently [ 84 ]. There is still a lot of unknown knowledge to discover.…”
Section: General Discussion Implications and Conclusionmentioning
confidence: 99%